2020
DOI: 10.3390/rs12223825
|View full text |Cite
|
Sign up to set email alerts
|

Applying Deep Learning to Clear-Sky Radiance Simulation for VIIRS with Community Radiative Transfer Model—Part 2: Model Architecture and Assessment

Abstract: A fully connected “deep” neural network algorithm with the Community Radiative Transfer Model (FCDN_CRTM) is proposed to explore the efficiency and accuracy of reproducing the Visible Infrared Imaging Radiometer Suite (VIIRS) radiances in five thermal emission M (TEB/M) bands. The model was trained and tested in the nighttime global ocean clear-sky domain, in which the VIIRS observation minus CRTM (O-M) biases have been well validated in recent years. The atmosphere profile from the European Centre for Medium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…An NN emulator that can be used in the RTM was developed some time ago (Chevallier et al., 1998) and was applied to the data assimilation system of the numerical weather prediction (NWP) model (Chevallier et al., 2000). The emulation studies in the RTM are still actively performing (Bue et al., 2019; Liang & Liu, 2020; Stegmann et al., 2022), eventually targeting to the aircraft‐satellite data assimilation in relation to the improvement of forward operator. Recent RTM emulator studies based on clear‐sky simulations have shown a of 1.87–10.88‐fold speedup (Liu et al., 2020) when used with the Rapid Radiative Transfer Model for GCMs (RRTMG; Iacono et al., 2008), and 1.8–3.5‐fold (Ukkonen et al., 2020) and up to 4‐fold (Veerman et al., 2021) for the RRTMG—Parallel scheme (Pincus et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…An NN emulator that can be used in the RTM was developed some time ago (Chevallier et al., 1998) and was applied to the data assimilation system of the numerical weather prediction (NWP) model (Chevallier et al., 2000). The emulation studies in the RTM are still actively performing (Bue et al., 2019; Liang & Liu, 2020; Stegmann et al., 2022), eventually targeting to the aircraft‐satellite data assimilation in relation to the improvement of forward operator. Recent RTM emulator studies based on clear‐sky simulations have shown a of 1.87–10.88‐fold speedup (Liu et al., 2020) when used with the Rapid Radiative Transfer Model for GCMs (RRTMG; Iacono et al., 2008), and 1.8–3.5‐fold (Ukkonen et al., 2020) and up to 4‐fold (Veerman et al., 2021) for the RRTMG—Parallel scheme (Pincus et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the relativistic loss aims to predict the probability that a real image is relatively more realistic than a fake one, as shown in Eq (5), which aids in learning shaper edges and more detailed textures. Furthermore, ESRGAN removes batch normalization (BN) [15], used in SRGAN, to further minimize artifacts in the generated image and employs a residual-in-residual dense block (RRDB) instead of the original residual block (RB) to improve training stability. All these advantages enable ESRGAN to effectively enhance image resolution at larger upscaling factors.…”
Section: B Overview Of Esrganmentioning
confidence: 99%
“…Deep Learning, in particular, has become one of the most widely used AI methods. Its applications in remote sensing and numerical weather prediction are currently being investigated [12][13][14][15][16][17]. The remote sensing image processing using a state-of-art convolutional neural network (CNN) [18][19][20][21][22][23] method has also become popular [24,25].…”
mentioning
confidence: 99%
“…Here, we used a multilayer neuron to calibrate the input features provided by the low-cost light sensors against the data provided by the Minolta reference sensor [ 35 , 36 , 37 ]. A multilayer neuron (MLP) is a class of feedforward artificial neural network (ANN).…”
Section: Machine Learning and Workflowmentioning
confidence: 99%